OP0181 MOLECULAR CHARACTERIZATION AND STRATIFICATION OF IDIOPATHIC INFLAMMATORY MYOPATHIES: ON THE BASIS OF SKELETAL MUSCLE TRANSCRIPTOME STUDY. (June 2019) - Chen, He; Lu, Xin; Shang, Jing-Zhe; Wu, Ai-Ping; Cheng, Gen-Hong; Lu, Ning; Peng, Qinglin; Wang, Guo-Chun
Abstract : Background: Idiopathic inflammatory myopathies (IIM) are a group of complicated heterogenous autoimmune diseases, to date, little is known about its skeletal muscle transcriptomic features. Objectives: Here, we performed skeletal muscle RNA-sequencing (RNA-seq) to discover the global muscle transcriptional signature of IIM based on myositis-specific antibodies (MSA) profiles and investigate the potential molecular pathway of IIM. Methods: Muscle specimen were taken from 60 patients with IIM, 6 patients with non-IIM myopathies and 9 healthy controls. The serum and PBMC samples were also obtained from the IIM patients at the time of muscle biopsy. For RNA-seq, IIM was dissected into eight groups based on their MSA profiles: MSA and ANA negative (n = 4), anti-synthetase antibodies positive (n= 13), -MDA5 positive (n = 6), -NXP-2 positive (n = 7), -TIF-1γ positive (n = 10), -SRP or anti-HMGCR positive (n = 6), -Mi-2 positive (n = 7), MSA negative but anti-Ro-52 positive (n = 7). RNA from muscle specimen were extracted according to manufactory guide and sequenced using Illumina HiSeq2500. Quantitative real-time reverse transcription-polymerase chain reaction (qRT-PCR) was performed on sequencing cohorts and expanding cohorts to validate the results of RNA-seq. Immunohistochemistry was also performed on muscle biopsy to determine the MxA expression in different MSA subgroups. Results: To define the global muscle signature of IIM, all IIM samples were compared to NC and total of 1637 transcripts were differentially expressed (log2 Fold Change > 1, Padj < 0.05). Unsupervised hierarchical clustering of these differentially expressed transcripts (DETs) revealed a prevalent interferon (IFN) signature and showed that 68 interferon-stimulated genes (ISGs) were significantly up-regulated in IIM. Then these 68 ISGs were used to cluster different MSA subgroups and distinct ISG expression was found. The mRNA expression levels of several ISGs (MX1, IFIH1, LAMP3, CMPK2, HERC6) in sequencing cohorts and expanding cohorts also confirmed the diverse ISG expression between different MSA subgroups. An IFN signature scoring system was established to quantify the IFN activity and subsequently IIM could be classified into IFN-Dominant, IFN-Moderate and IFN-Weak respectively based on the IFN intensity and different MSA subgroup. Moreover, the IFN-Dominant group showed much higher MxA expression on muscle biopsy than the IFN-Moderate and IFN-Weak group by immunohistochemistry. Conclusion: We revealed a prominent IFN signature and MSA-based ISG expression heterogeneity in IIM through muscle transcriptomics. Preliminary results showed that the IFN muscle signature may play a predominant role in some subgroups but not all IIM groups in the pathogenesis of IIM. References: [1] Miller FW, Lamb JA, Schmidt J, Nagaraju K. Nat Rev Rheumatol. 2018 Apr 20;14(5):255-268. [2] Mariampillai K, Granger B, Amelin D, Guiguet M, Hachulla E, Maurier F, Meyer A. JAMA Neurol. 2018 Dec 1;75(12):1528-1537. [3] Banchereau R, Hong S, Cantarel B, Baldwin N, Baisch J, Edens M, Cepika AM. Cell. 2016 Apr 21;165(3):551-65. Disclosure of Interests: None declared